Microbial Interactions in Food Fermentation: Interactions, Analysis Strategies, and Quality Enhancement - Wenjing Liu; Yunxuan Tang; Jiayan Zhang; Juan Bai; Ying Zhu; Lin Zhu; Yansheng Zhao; Maria Daglia; Xiang Xiao; Yufeng He (Foods, 2025)
Food fermentation is driven by microbial interactions. This article reviews the types of microbial interactions during food fermentation, the research strategies employed, and their impacts on the quality of fermented foods. Microbial interactions primarily include mutualism, commensalism, amensalism, and competition. Based on these interaction patterns, the safety, nutritional composition, and flavor quality of food can be effectively improved. Achieving precise control of fermented foods’ qualities via microbial interaction remains a critical challenge. Emerging technologies such as high-throughput sequencing, cell sorting, and metabolomics enable the systematic analysis of core microbial interaction mechanisms in complex systems. Using synthetic microbial communities and genome-scale metabolic network models, complicated microbial communities can be effectively simplified. In addition, regulatory targets of food quality can be precisely identified. These strategies lay a solid foundation for the precise improvement of fermented food quality and functionality.